2021
DOI: 10.1111/ijac.13945
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat treatment temperature on the properties of the lithium disilicate‐fluorcanasite glass‐ceramics

Abstract: This study aims to investigate the influence of heat treatment temperatures on the mechanical properties and chemical solubility (CS) of lithium disilicate‐fluorcanasite glass‐ceramics and to develop new dental materials. The glasses and glass‐ceramics were prepared using CaF2‐SiO2‐CaO‐K2O‐Na2O‐Li2O‐Al2O3‐P2O5‐based glass system using a conventional melt quenching method followed by a two‐stage crystallization process. This two‐stage method involves two heating temperature steps: first at a constant temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…At the temperature within the first exothermic peak of DTA (~700 °C), LD was detected in addition to LM formation as main phase. The result was different from previous studies (Soares et al, 2015;Zhang et al, 2015;Kraipok et al, 2022), which LD could only be transformed from LM at higher temperature. Additionally, Li 3 PO 4 was not detected because the amorphous form existed at low temperature, with less size and content (Höland et al, 2006;Sun et al, 2021).…”
Section: Effects Of Heat Treatment On Microstructure and Flexural Str...contrasting
confidence: 99%
“…At the temperature within the first exothermic peak of DTA (~700 °C), LD was detected in addition to LM formation as main phase. The result was different from previous studies (Soares et al, 2015;Zhang et al, 2015;Kraipok et al, 2022), which LD could only be transformed from LM at higher temperature. Additionally, Li 3 PO 4 was not detected because the amorphous form existed at low temperature, with less size and content (Höland et al, 2006;Sun et al, 2021).…”
Section: Effects Of Heat Treatment On Microstructure and Flexural Str...contrasting
confidence: 99%
“…By modifying the compositions, the biological activity of the modified glass-ceramics can be significantly increased [23,24]. The addition of lithium disilicate increases the chemical resistance of fluorcanasite-based glass-ceramics [25,26]. Vyas et al (2022) [27] found out that with increased fluorcanasite content in the composition, hydrophilicity also increases over the entire surface of the sample, and, subsequently, cell adhesion and proliferation is raised.…”
Section: Introductionmentioning
confidence: 99%
“…The main influencing factors affecting this process include chemical composition and heat treatment. [16][17][18][19] Previous studies claimed that SiO 2 is the primary oxide in silicate glass, and the glass structure featured a significant impact on the material properties. 20,21 CaO act as a network modifier in the silicate network, which can destroy the bridge oxygen bond of Si-O-Si units.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallization behavior of the basic glass is mainly affected by nucleation and crystal growth. The main influencing factors affecting this process include chemical composition and heat treatment 16–19 . Previous studies claimed that SiO 2 is the primary oxide in silicate glass, and the glass structure featured a significant impact on the material properties 20,21 .…”
Section: Introductionmentioning
confidence: 99%